Relationships between the Regulatory Systems of Quorum Sensing and Multidrug Resistance - Xu, Gang-Ming (Frontiers in Microbiology, 2016)
Cell-cell communications, known as quorum sensing (QS) in bacteria, involve the signal molecules as chemical languages and the corresponding receptors as transcriptional regulators. In Gram-negative bacteria, orphan LuxR receptors recognize signals more than just acylhomoserine lactones (AHLs), and modulate interspecies and interkingdom communications. Whereas, in the Gram-positive Streptomyces, pseudo gamma-butyrolactones (GBLs) receptors bind antibiotics other than GBL signals, and coordinate antibiotics biosynthesis. By interacting with structurally diverse molecules like antibiotics, the TetR family receptors regulate multidrug resistance (MDR) by controlling efflux pumps. Antibiotics at subinhibitory concentration may act as signal molecules; while QS signals also have antimicrobial activity at high concentration. Moreover, the QS and MDR systems may share the same exporters to transport molecules. Among these orphan LuxR, pseudo GBL receptors, and MDR regulators, although only with low sequence homology, they have some structure similarity and function correlation. Therefore, perhaps there might be evolutionary relationship and biological relevance between the regulatory systems of QS and MDR. Since the QS systems become new targets for antimicrobial strategy, it would expand our understanding about the evolutionary history of these regulatory systems.